PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI NONFINANSIAL TERHADAP TENAGA KERJA PERUSAHAAN (STUDI PADA SPBU BS GROUP) - Wishnuwardhana R. Ismantara; Fransisca Desiana Pranatasari (Business Management Journal, 2019)
The increasing number of motorized vehicles from year to year triggers the high number of gas stations, and consequently, a more competitive sector. As service business, gas stations must pay attention to the workforce’s performance in order to excel in the competition. This research is  conducted to determine the influence of financial and non-financial compensation on the workforce’s performance in BS Group. This research is a quantitative research. The population of this research is the entire operator department of BS Group. This research uses non-probability sampling method, or more specifically, saturated sampling, to select 83 respondents as samples. The questionnaires used as data collection method consist of three variables, namely financial compensation, non-financial compensation, and performance. Additionally, Multiple Linear Regression is used as data analysis technique. Research results indicate that both financial and non-financial compensations significantly affect the employee performance of BS Group. Keywords: Financial compensation, Non-financial compensation, Performance, Labor.